Catalytic Hydrodeoxygenation of High Carbon Furylmethanes to Renewable Jet‐fuel Ranged Alkanes over a Rhenium‐Modified Iridium Catalyst. Issue 16 (27th July 2017) - Liu, Sibao; Dutta, Saikat; Zheng, Weiqing; Gould, Nicholas S.; Cheng, Ziwei; Xu, Bingjun; Saha, Basudeb; Vlachos, Dionisios G.
Abstract: Renewable jet‐fuel‐range alkanes are synthesized by hydrodeoxygenation of lignocellulose‐derived high‐carbon furylmethanes over ReO x ‐modified Ir/SiO2 catalysts under mild reaction conditions. Ir−ReO x /SiO2 with a Re/Ir molar ratio of 2:1 exhibits the best performance, achieving a combined alkanes yield of 82–99 % from C12 –C15 furylmethanes. The catalyst can be regenerated in three consecutive cycles with only about 12 % loss in the combined alkanes yield. Mechanistically, the furan moieties of furylmethanes undergo simultaneous ring saturation and ring opening to form a mixture of complex oxygenates consisting of saturated furan rings, mono‐keto groups, and mono‐hydroxy groups. Then, these oxygenates undergo a cascade of hydrogenolysis reactions to alkanes. The high activity of Ir−ReO x /SiO2 arises from a synergy between Ir and ReO x, whereby the acidic sites of partially reduced ReO x activate the C−O bonds of the saturated furans and alcoholic groups while the Ir sites are responsible for hydrogenation with H2 . Abstract : The difference is plane : Renewable jet‐fuel‐range alkanes are synthesized in 82–99 % yield by hydrodeoxygenation of lignocellulose‐derived furylmethanes over Ir−ReO x /SiO2 catalysts under mild reaction conditions. The high catalyst activity arises from synergy between Ir and ReO x, whereby the acidic sites of partially reduced ReO x activate the C−O bonds of the saturated furans and alcoholic groups, while the Ir sites are responsible for hydrogenation.